Faktor Risiko dan Prevalensi Gangguan Muskuloskeletal pada Bahu di Sektor Konstruksi: Literatur Review - Rohmah, Rizka Lailatul; Baiduri Widanarko (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Musculoskeletal disorders affecting the shoulder are a prevalent health issue in the construction sector, leading to reduced productivity and quality of life among workers. This study aims to identify risk factors and the prevalence of shoulder pain in construction workers through a systematic literature review. A literature review was conducted following PRISMA guidelines, with searches performed in five major databases: Scopus, PubMed, Taylor & Francis Online, ProQuest, and Science Direct. Out of 1,628 initially identified articles, seven studies met the inclusion criteria and were analyzed further. The findings indicate that the prevalence of shoulder pain among construction workers ranges from 18.3% to 72%, with key risk factors including non-ergonomic working postures, repetitive tasks, manual handling, high body mass index, advanced age, and psychosocial stressors. Additionally, environmental factors such as heat strain were found to contribute to the increased risk of shoulder pain. However, regular physical activity serves as a protective factor in reducing the risk of musculoskeletal disorders..